Formulation Sunscreen Emulgel of Sweet Potatoes Leaves Extract (Ipomoea batatas (L.)) Antin-3 Variety - Dipahayu, Damaranie (Akademi Farmasi Surabaya, 2020)
Ultraviolet radiation intensively causes oxidation and premature skin aging. UV B radiation causes sunburn and pigmentation. Sunscreen is used to protect the skin due to excessive sun UV exposure. The purpose of this study was to determine the physical characteristics and SPF value of emulgel containing purple sweet potatoes leaves extract (Ipomoea batatas (L.)) Antin-3 variety. Determination of the SPF value using the UV-VIS spectrophotometer method. Both of Antin-3 emulgel and base emulgel were not show phase separation after mechanically tested. Their not only had a homogeneous and soft consistency but also fresh on the skin. Antin-3 emulgel had a light brown colour and leaves extract scent while base emulgel had a white colour and base scent. Spread capacity and pH value of Antin-3 emulgel and base emulgel in a row were 3.6 cm; 6.28 and 3.2 cm; 6.41. SPF value of Antin-3 emulgel was 6.50 and base emulgel was 1.17. Antin-3 emulgel have extra potency to protect against UV B radiation.